Global knowledge structure, international political economy and justice. Media and information warfare international conference: a global challenge in the 21st century (m-i-war2007) / Yuslinda Mat Yassin and Munis Paran - Mat Yassin, Yuslinda; Paran, Munis (Centre for Media and Information Warfare Studies, 2008)
As the 21st century is in its first decade, it appears that the "centre cannot hold" and "things are falling apart". The world is full of inequities. The notion of sovereignty of state is becoming untenable. The world is dominated by one super power with overwhelming political, economic, military and cultural superiority. About forty transnational industrial and media conglomerates dominate the economies and resources of the global with impunity, being answerable, generally to no one. Eight or nine well developed economies are getting more than a fair deal from the world economy. About 25 middle level, well-developed states are quite capable of drawing policies for a comfortable future. The rest of the states of the world, about 160 or so are not in a position to plan for a better future. In fact some of the states' future itself are in jeopardy. "Most of the poor one billion people are in 50 countries, 70% of them in Africa and most of the rest in central Asia. Some developing states are growing. Most of the developing states are confronted with wars, and misuse of natural resources. Some are land locked with no access to the outside world. A few are under the rule of kleptocracy and pluctocracy.